IMPACT OF ACTIVE MILITARY ACTIONS ON THE ECOLOGICAL STATE OF SOIL AND WATER RESOURCES IN SOUTHERN UKRAINE - SHYBANOVA, ALLA; RUDA, MARIIA; PASLAVSKYI, MYKHAILO (Herald of Khmelnytskyi National University. Technical sciences, 2025)
Assessment of the Environmental Condition is Essential for Effective Post-War Recovery and Forms the Basis for Determining Reparations Payable by Russia. The purpose of this study is to investigate the impact of active military operations on the environmental condition of water and soil resources in southern Ukraine, using the example of the city of Snihurivka in the Mykolaiv region. The study also aims to develop recommendations for minimizing the consequences of combat activities on water resources and restoring land productivity. The destruction of industrial and infrastructure facilities in Snihurivka poses a serious environmental risk, particularly due to potential leaks of petroleum products, chemicals, and industrial pollutants. The destruction of critical infrastructure due to explosive weapons has created environmental risks. In Snihurivka, explosive weapons have caused significant damage to key infrastructure, including sewage treatment facilities, water towers, and pumping stations; the railway station; industrial enterprises, agricultural farms, and irrigation canals; energy facilities; and residential and administrative buildings. The water quality in the Inhulets River has significantly deteriorated due to pollution from mine waters and industrial wastewater from Kryvyi Rih. Damage to the sluices of the Karachunivka Dam as a result of a missile strike by Russian forces has made it impossible to control water discharge, exacerbating the river’s pollution problem. The use of explosive weapons has altered the physical, chemical, and biological properties of the soil. Heavy metals and polycyclic aromatic hydrocarbons have been detected in soil samples at concentrations exceeding permissible levels in Ukraine. Maximum allowable concentrations (MAC) were exceeded by 1.2 to 11 times for the following elements: phosphorus (P), arsenic (As), lead (Pb), copper (Cu), cadmium (Cd), zinc (Zn), nickel (Ni), barium (Ba), and benzo(a)pyrene. The increase in allowable levels of these elements is associated with the use of certain types of ammunition. A comprehensive approach to improving soil environmental conditions should include a more detailed study of the long-term impact of pollution on agricultural land and ecosystems, as well as monitoring and remediation of soils in areas with the highest pollution levels.